Socio-Economic Improvement of MSMEs through Digital Transformation in Metro City - Elita Yuni Setiyarini; Titin Rosdyanti; Meli Yana Puspita Sari (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study analyzes the impact of digital transformation on the socioeconomic welfare of MSMEs, including income growth, access to resources, quality of life, and business sustainability. Methodology/approach: This study used a mixed-methods explanatory sequential approach. The research population comprised 23,854 MSMEs in Metro City. This study employed a mixed-methods approach. Quantitative data were gathered from 100 respondents, selected via convenience sampling using the Slovin formula, and analyzed using Structural Equation Modeling (SEM). Qualitative insights were obtained through in-depth interviews with 15 purposively sampled MSME actors, and the data were examined through thematic analysis. Results: Digital transformation had a positive and significant effect on all dimensions of the socio-economic welfare of MSMEs. Conclusions: This study concludes that digital transformation has a positive impact on the socioeconomic welfare of MSMEs in Metro City by increasing income, access to resources, quality of life, and business sustainability. Limitations: This study focused on certain variables related to digitalization, whereas many other external factors that may have influenced the results were not explored in depth. Contribution: This research provides practical contributions to MSMEs and policymakers by demonstrating the positive impact of digital transformation on business prosperity. Academically, this study enriches the fields of digital management and economics through a holistic approach in the local MSME context.